2020
DOI: 10.3171/2020.5.peds2058
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and developmental outcomes after pediatric insular epilepsy surgery for focal cortical dysplasia

Abstract: OBJECTIVECognitive risk associated with insular cortex resection is not well understood. The authors reviewed cognitive and developmental outcomes in pediatric patients who underwent resection of the epileptogenic zone involving the insula.METHODSA review was conducted of 15 patients who underwent resective epilepsy surgery involving the insular cortex for focal cortical dysplasia, with a minimum follow-up of 12 months. The median age at surgery was 5.6 years (range 0.3–13.6 years). Developmental/intelligence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…[37][38][39] While major technological advances have made microsurgical resection for IE safer, permanent neurological impairment (eg, hemiplegia) rates exceed 20% in some contemporary series. 32,40 Characterizing the rate of transient and permanent deficits and their predictors may address concerns for the safety of surgery for IE and facilitate patient counseling. The identification of patient or operative variables associated with postoperative neurological deficits has the potential to refine surgical indications or modify the surgical technique, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] While major technological advances have made microsurgical resection for IE safer, permanent neurological impairment (eg, hemiplegia) rates exceed 20% in some contemporary series. 32,40 Characterizing the rate of transient and permanent deficits and their predictors may address concerns for the safety of surgery for IE and facilitate patient counseling. The identification of patient or operative variables associated with postoperative neurological deficits has the potential to refine surgical indications or modify the surgical technique, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 describes the studies that reported neuropsychological outcomes ( n = 32, 40%). A total of 36 different named neuropsychological outcome metrics were used, the Wechsler Intelligence Scale for Children (WISC) and its various versions being the most common ( n = 15, 47%) 23–32 . Eight (25%) of these studies did not specify how their neuropsychological outcomes were measured but generically stated a postoperative neuropsychological assessment was performed 33–40 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 different named neuropsychological outcome metrics were used, the Wechsler Intelligence Scale for Children (WISC) and its various versions being the most common (n = 15, 47%). [23][24][25][26][27][28][29][30][31][32] Eight (25%) of these studies did not specify how their neuropsychological outcomes were measured but generically stated a postoperative neuropsychological assessment was performed. [33][34][35][36][37][38][39][40] Of the 36 named metrics, 6 (17%) have been validated and 3 (8%) had reliability studies performed (see Table 2) for pediatric patients with epilepsy.…”
Section: Neuropsychological Outcomesmentioning
confidence: 99%
“…The VI was represented by the verbal comprehension score in the WAIS or WISC or by the standardized value of the averaged sub-scores on language comprehension and language expression in KIDS [ 14 ]. The WMI was represented by the working memory score in the WAIS and WISC.…”
Section: Methodsmentioning
confidence: 99%